Mutaciones del gen RAD51 en el cáncer familiar de ovario: revisión de la literatura (2015)
Background: In the last fifteen years, familiar ovarian carcinoma has been related to BRCA 1 and 2 mutations. However, 25% of new cases of ovarian neoplasm are explained by isolated genes involved in the mechanism of homologous recombination. Patients with family history of ovarian and breast carcinoma, negative for BRCA mutations and at least with one case of invasive ovarian carcinoma have been identify with monoallelic mutations in RAD51. Objective: To describe mutations on RAD51 complex, in order to identify its role in familiar ovarian cancer. Methodology: A systematic review of the literature of the last ten years involving the main data bases and using the following MeSH terms: “RAD51”, “ovarian cancer”, “ovarian neoplasm”, “family ovarian cancer”. Results: Prevalence reported for RAD51 mutation is between 0.2 and 2.5%, associated with the ethnicity of the population involved. Also is considered a cause for high grade serous ovarian carcinoma in women between 57 and 60 years old. RAD51C and RAD51D germ line mutations are related to ovarian-breast hereditary syndrome, in negative population for BRCA 1 and 2 mutations. Conclusion: Patients with RAD51 mutations, negative for BRCA mutation are associated with ovarian-breast cancer syndrome increasing the risk just for ovarian cancer.